Influence of Long Boreholes Layout and Drilling Length on Gas Drainage Based on Multifield Coupling Model of Gas-Bearing Coal. (17th November 2021) - Feng, Renjun
Abstract : Gas drainage through long seam boreholes is an effective method to prevent gas disasters in coal mines. In this paper, a multifield coupling model of gas migration in gas-bearing coal was first established. Then, a quantitative characterization method of gas drainage effect was put forward. Finally, the extraction effect of long boreholes was obtained under different layouts and drilling lengths. The research results show that, under the arrangement of long boreholes along the seam, the gas pressure around the borehole decreases significantly with the extraction time. There is no extraction blank in the middle of the working face. However, it is easy to cause uneven gas drainage in the combined arrangement of the long boreholes along the seam and the penetrating boreholes. Furthermore, it is found that the drainage volume of the long boreholes along the seam is similar to that of the joint layout under the same drainage time. As the length of the borehole increases, the influencing range of gas drainage increases. When the borehole lengths are 150 m and 240 m, the drainage volumes are about 1.31 and 2.50 times that of the 90 m boreholes, respectively. The research achievements could provide a specific reference for the layout of long boreholes along the bedding and the determination of reasonable parameters for gas drainage on site.